Quantitative dataset of shallow water reef in Pulau Bidong, Southern of South China sea during pre and post of tropical storm (Pabuk - January 2019) - Zainudin Bachok; Che Din Mohd Safuan; Nur Hidayah Roseli; Mohd Fadzil Akhir (Data in Brief, 2020)
This article provides raw datasets of the coral reefs status in Pulau Bidong, southern of South China Sea before and after being strike by the tropical storm Pabuk on January 2019. Data were collected using a rapid coral survey method called Coral Video Transect (CVT) technique. The data were collected along a 100 m transect line set up parallel to the shoreline and at a constant depth. In total, eight transects were surveyed during both periods (pre – August 2016, post – March 2019). Back in laboratory, the footage was then extracted into non-overlapping frames or still images prior to image analysis using Coral Point Count with Excel Extension (CPCe) software. The benthic coral reefs relative percentage cover was automatically generated after the image analysis and represented by five major categories; live coral (C), algae (ALG), other invertebrates (OT), dead coral (DC), and sand silt and rock (SR). Live coral cover was identified up to the genus level. This raw dataset was used in this article. The data provided in this article could be of significant use for future studies especially on coral recovery after the natural disturbances. It can provide a baseline assessment especially for coral reefs management as well as to comprehend changes in coral health status in the face of natural and anthropogenic disturbances. The data presented here support the information in the article Safuan et al. (2020).